PENGUATAN KARAKTER PEDULI SOSIAL DALAM PEMBELAJARAN PAI SISWA KELAS VI SDN 1 SAMBA KATUNG KABUPATEN KATINGAN KALIMANTAN TENGAH - Taufik Rahman; Mazrur Mazrur; Abdul Gofur (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
Character education in schools is very important in forming students' dignified and socially aware personalities. One of the characters that needs to be instilled is social awareness, which can be implemented through Islamic Religious Education (PAI) subjects. This study aims to analyze the strengthening of social awareness characters in grade VI students of SDN 1 Samba Katung, Katingan Regency, Central Kalimantan through the material "The Beauty of Helping Each Other" which is taken from the values ​​in Surah Al-Maidah verses 2 and 3. The method used in this study is qualitative descriptive, with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that PAI learning that teaches helping each other in goodness and avoiding sin and hostility can strengthen students' social awareness characters. In addition, the implementation of this material in schools has succeeded in encouraging students to help each other in various social activities, although there are still some students who have not fully applied the character. Thus, strengthening social awareness characters through PAI learning can create students who care more about others, appreciate differences, and contribute to a harmonious community life.